2013
DOI: 10.1007/s10096-013-1942-5
|View full text |Cite
|
Sign up to set email alerts
|

Alarming incidence of genital mycoplasmas among HIV-1-infected MSM in Jiangsu, China

Abstract: Males who have sex with men (MSM) are considered at high risk of blood-borne and sexually transmitted infections (STIs), mainly due to the practice of unsafe sex, often combined with drug use and needle-sharing. A cross-sectional study was designed for the detection of genital mycoplasmas during the period from March 2009 to May 2010 in Jiangsu province. This work was approved by the Research ethics Committee of Jiangsu Centers for Diseases Prevention and Control (CDC), and written consent was obtained from al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Studies have focused primarily on Mycoplasma genitalium and have reported conflicting prevalence levels in comparison to other common STIs. [7][8][9] Even though such studies have suggested the need to screen MSM for M. genitalium, most routine laboratories do not provide this service. 7,10 Low prevalence rates of Ureaplasma species and Mycoplasma hominis have been reported in rectal specimens from MSM; however, this has been confounded by the use of insensitive culture-dependent methods.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have focused primarily on Mycoplasma genitalium and have reported conflicting prevalence levels in comparison to other common STIs. [7][8][9] Even though such studies have suggested the need to screen MSM for M. genitalium, most routine laboratories do not provide this service. 7,10 Low prevalence rates of Ureaplasma species and Mycoplasma hominis have been reported in rectal specimens from MSM; however, this has been confounded by the use of insensitive culture-dependent methods.…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale survey in MSM showed that CRF55_01B was found in 7 from 11 studied provinces in China [53, 54]. A recent paper reported that an outbreak prevalence of the CRF55_01B strains among MSM has formed in Shenzhen, a large city in Southern China [53, 55, 56]. The identification of CRF55_01B in MSM in Yinchuan indicates that MSM is the most at-risk population for the emergence of new HIV subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In the available studies of MG infection in men living in China, the positive rate was 3.4% as detected in first-void urine (FVU) and 5.4% as detected in the rectal samples of men who have sex with men (MSM) in Shenzhen [ 14 ], 15.3% in the rectal samples of MSM in Shenyang [ 15 ]. Among men living with HIV in Jiangsu Province, the positive rate ranged from 20.1 to 29.2% as detected in FVU [ 16 19 ]. The positive rate of MG was 10.2% in symptomatic patients with NGU and 13.9% in patients with asymptomatic NGU in Hong Kong [ 20 , 21 ] and was 28.1% in men with STD-related complaints in Guangxi [ 22 ].…”
Section: Introductionmentioning
confidence: 99%